KEPUTUSAN PEMBELIAN DAN SIKAP KONSUMEN ROTI MEREK SARI ROTI (Studi Kasus pada Mahasiswa S1 Institut Pertanian Bogor) - Risa Martha Muliasari; Dwi Rachmina (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2015)
Sari Roti is a bakery product produced by Nippon Indosari Corpindo. The purposes of this research are to describe characteristics of consumers, analyze the process of consumer’s desicion making and also to analyse the consumer attitudes towards Sari Roti’s product attributes. Methods used include Descriptive Analysis and Fishbein Multi-Attitude Model involving one hundred respondents of BAU’s undergraduate students. The samples are purposively selected on the basis that most of students prefer to eat Sari Roti in the morning or during the break time. Most of the consumers of Sari Roti are women, 18 to 22 years old, where their monthly allowance (IDR 500,000 to 999,999) comes from parents. Descriptive Analysis shows that in general, five stages of purchasing decision were passed. Overall, result of consumers’s attitude towards Sari Roti brand is positive based on Fishbein Multi-attribute Attitude Model. Clarity of expiry date of the product become the most important attribute of consideration. However, attribute of price should be taken into consideration, as it obtained smallest evaluation score and will determine how many purchases are made.